Adaptasi dan Pengujian Alat Ukur Complex Thinking-21 Scale di Indonesia - Joti Cherryelle Rizky Yanto Soemantri; Muhammad Ihsan Fadhilah; Salma Dinna Amalia Putri; Yuda Akbari; Diah Zaleha Wyandini; Ghinaya Ummul Mukminin Hidayat (Universitas Kristen Maranatha, 2025)
Complex Thinking is a cognitive process for understanding the relationship between unity and diversity. This process involves interdisciplinary skills that are important for students in the context of education and professional life preparation. However, until now, no adaptation of the Complex Thinking measurement tool has been conducted in Indonesia. Therefore, a study is needed to examine the validity and reliability of the Complex Thinking measurement tool adapted from Tobon (2021) in the Indonesian context. The Complex Thinking scale consists of 21 items with 5 dimensions: problem solving, critical analysis, metacognition, system analysis, and creativity. This study involved 203 active university students as participants. The results of the CFA test indicated that the model was fit, with goodness-of-fit indices of 0.067 (RMSEA), 0.062 (SRMR), and 0.994 (CFI). These findings confirm that the Complex Thinking measurement tool adapted into Indonesian has good validity. Furthermore, with a Cronbach's Alpha coefficient of 0.885, the measurement tool has proven to be reliable.